THE ROLE OF LANGUAGE LEARNING STYLES AND STRATEGIES IN EFL CLASSES - Tukhliboeva Dilbarkhan Khalimjon kizi; Advisor: Erkulova Feruza Melikuziyevna (Web of Journals Publishing, 2025)
When teaching students a foreign language, EFL instructors should consider both their students' proficiency level and learning styles. By assessing their background knowledge and language acquisition abilities, teachers can determine how and what to teach effectively. It is important for the teaching approach to be engaging and relatively stress-free. This article delves into various challenges and typical developmental trends associated with creatively teaching English as a second language. The initial section of the article offers insight into the diverse learning styles of students who encounter difficulties with the language. Subsequently, it synthesizes the results from a study that compared skill acquisition, including listening, reading, writing, and speaking, in a text-based learning style setting. The detailed activities highlighted are tailored towards facilitating a smoother learning process through innovative teaching methods.
Keywords: Learning styles, school pupils, learning strategies, The VARK questionnaire.